Perancangan Aplikasi Permainan Let’s Say dengan Interaksi Pengenalan Ucapan - Andhika Dewanta; R. Rizal Isnanto; Kurniawan Teguh Martono (Jurnal Teknologi dan Sistem Komputer, 2015)
Computer games has been widespread. Currently, almost all devices that have a screen can play the game with the experience of interactivity to entertain the public. The game does not always have a negative effect. Game application that has a learning function will be useful and easily accepted by society. This study was conducted to determine how computer games can be a fun medium of information and learning by making use of speech recognition interaction. The application development of this "Let's Say" game is done by using the method of multimedia development consisting stages of concept, design, material collection, implementation, testing, and distribution. The design of the application is done using UML modeling and ERD. Application development is done using Visual Basic.NET programming language, WPF system interface, and SQLite database. Application utilizes Windows Speech Recognition as a speech recognition engine. Functional testing of the application is done using black box methods. Applications testing to users is done through a questionnaire. The test results showed that the application works well according to functions that has been specified. Application testing to users indicate that the application is informative and easy to use with a view that is quite interesting. Tests also showed that the use of speech recognition has been going well and helpful.